Faith, nationalism, and the future of liberal democracy. - Elcott, David M. (University of Notre Dame Press, 2021)
"David Elcott, C. Colt Anderson, Tobias Cremer, and Volker Haarmann present a pragmatic and modernist exploration of how religion engages in the public square. Elcott and his co-authors are concerned about the ways religous identity is being used to foster the exclusion of individuals and communities from citizenship, political representation, and a role in determining public policy. They examine the ways religious identity is weaponized to fuel populist revolts against a political, social, and economic order that values democracy in a global and strikingly diverse world ... The authors explore what constitutes a constructive religious voice in the political arena, even in nurturing patriotism and democracy, and what undermines and threatens liberal democracies. To lay the groundwork for a religious response, the book offers chapters showing how Catholicism, Protestantism, and Judaism can nourish liberal democracy. The authors encourage people of faith to promote foundational support for the institutions and values of the democratic enterprise from within their own religious traditions and to stand against the hostility and cruelty that historically have resulted when religious zealotry and state power combine"--The publisher
Keywords: Religion and politics -- United States.; Religion and politics -- Europe.; Liberalism -- Religious aspects.; Democracy -- Religious aspects.; Free enterprise -- Religious aspects.; Religion et politique -- États-Unis.; Religion et politique -- Europe.; Libéralisme -- Aspect religieux.; RELIGION / Religion, Politics & State; Free enterprise -- Religious aspects; Democracy -- Religious aspects; Liberalism -- Religious aspects; Religion and politics; Europe; United States